POPULATION VARIATION OF ENDOPHYTIC ACTINOMYCETE IN SOYBEAN (GLYCINE MAX (L) MERRIL) - JITENDRA DALAL; NIKHILESH KULKARNI (The Bioscan, 2012)
Present investigation was carried out to study variation in endophytic actinomycete population colonizing soybean cultivated in vertisol. Endophytic population was assessed at different growth stages of soybean (C.V. JS- 335) viz., vegetative and reproductive stages. A 186 (25.86 %) isolates were obtained from vegetative growth stages (V1-V5) and 533 (74.13 %) from reproductive growth stages. As plant grows the endophytic population increases progressively however, at the onset of reproductive stages viz., R1-R8 the endophytic population starts to decrease and attains a stable value at R8 stage. The maximum endophytic population was found at V4-V5 stages (1.83±0.05 and 1.89±0.06) and R1-R3 stages (1.80±0.03, 1.78±0.04 and 1.74±0.03) at which the plant attains maturity. Our investigation provides a valuable insight in understanding of endophytic microorganisms in their unique ecological habitat.